Sepiapterin reductase deficiency: a treatable mimic of cerebral palsy - Friedman, Jennifer R.; Hoffmann, Georg F.; Lutz, Thomas; Blau, Nenad (Annals of neurology, 2011)
Objective: Sepiapterin reductase deficiency (SRD) is an under-recognized levodopa-responsive disorder. We describe clinical, biochemical, and molecular findings in a cohort of patients with this treatable condition. We aim to improve awareness of the phenotype and available diagnostic and therapeutic strategies to reduce delayed diagnosis or misdiagnosis, optimize management, and improve understanding of pathophysiologic mechanisms. Methods: Forty-three individuals with SRD were identified from 23 international medical centers. The phenotype and treatment response were assessed by chart review using a detailed standardized instrument and by literature review for cases for which records were unavailable. Results: In most cases, motor and language delays, axial hypotonia, dystonia, weakness, oculogyric crises, and diurnal fluctuation of symptoms with sleep benefit become evident in infancy or childhood. Average age of onset is 7 months, with delay to diagnosis of 9.1 years. Misdiagnoses of cerebral palsy (CP) are common. Most patients benefit dramatically from levodopa/carbidopa, often with further improvement with the addition of 5-hydroxytryptophan. Cerebrospinal fluid findings are distinctive. Diagnosis is confirmed by mutation analysis and/or enzyme activity measurement in cultured fibroblasts. Interpretation: Common, clinical findings of SRD, aside from oculogyric crises and diurnal fluctuation, are nonspecific and mimic CP with hypotonia or dystonia. Patients usually improve dramatically with treatment. Consequently, we recommend consideration of SRD not only in patients with levodopa-responsive motor disorders, but also in patients with developmental delays with axial hypotonia, and patients with unexplained or atypical presumed CP. Biochemical investigation of cerebrospinal fluid is the preferred method of initial investigation. Early diagnosis and treatment are recommended to prevent ongoing brain dysfunction. ANN NEUROL 2012;